Analysis of Uncommon Negative Cloud-to-Ground Lightning Flashes Event Within Two Seconds - Zikri Abadi Baharudin, Abdul Rahim Mohamed Ismail, Hidayat Zainuddin (International Journal of Advanced Science and Technology, 2020)
The number of 938 whole flashes which composed of 799 negative ground flashes (-CG), 26 positive ground flashes (+CG) and 113 cloud flashes were analyzed in a form of wideband radiation electric field. The number of 748 samples of whole flashes for -CG  were found to have the return strokes less than 1 seconds which are considered as typical case. However, from 51 out of 799 samples of the whole flashes for negative cloud-to-ground flashes were considered rare where some numbers of the return strokes appeared after 1 second. These profiles are counted to be 6 % and can be considered as a unique or uncommon whole flashes event.  Furthermore, from 51 of uncommon whole flashes event, the number of strokes varies from 4 to 19 strokes.